Study on the effect of propolis extracted by ethanol or water on acute inflammation in animals based on model tests - HU Fu-liang; LI Ying-hua; CHEN Min-li; YING Hua-zhong; ZHU Wei (浙江大学学报. 农业与生命科学版)
The antiinflammatory effects of propolis extracted by ethanol and water was studied. The results showed that propolis extracted by either water or ethanol were endowed with quite evident antiinflammatory effect. It seems that the antiinflammatory effects of the two extracts are caused by somewhat different mechanisms and that water extracted propolis contains functional components other than flavonoids.